Kant in Brazil - Rauscher, Frederick, 1961-; Perez, Daniel Omar (North American Kant Society studies in philosophy., 2012)
Presents for the first time in English a selection of the best papers written by Brazilian Kant scholars. The thriving Brazilian Kant community produces exceptional work on all aspects of Kant's philosophy contributing significantly to the worldwide debate on Kant's philosophy.